A Study on Feasibility of Digital Marketing for Small and Medium Enterprises - Maney, Kiran L; Sindhuja, A.; Mathews, Soney (Archers & Elevators Publishing House, 2015)
Today is the era of information technology. The dependency on technology in all aspects of work and personal life has made the marketers to adopt different means to reach out to their tech savvy consumers. The concept of digital marketing has witnessed an accelerated growth over the past decade. Digital marketing is a technique of marketing which embraces the use of devices such as smart phones, personal computers, tablets and cell phones to connect with customers. The reduced expenses and the eventual high return on investment provided by digital marketing is inducing a larger number of companies to resort to this marketing practice. Small and Medium enterprises who do not have sufficient access to funds to outlay for convention means of promotion such as print, television, personal selling could benefit the most by implementing this technique. Although incorporating digital marketing techniques appears to be very straightforward, for SMEs there are various intricacies and challenges in its adoption. These intricacies emerge on account of the unique business models embraced by the SMEs of diverse sectors. This research paper highlights the understanding and feasibility of adopting digital marketing techniques by SMEs in India. The outcome of the study presents the benefits that would be conferred on the SMEs in India which would enable them to capitalize on the advantages of digital marketing.